Dinamika Kelembagaan Koperasi Program Kemitraan Inti-Plasma Perkebunan Kelapa Sawit - Zulkifli (Jurnal Ekonomika: Manajemen, Akuntansi, dan Perbankan Syari'ah, 2025)
This study explores the institutional dynamics of cooperatives within the core-plasma partnership program in the oil palm plantation sector in East Kalimantan. The program is designed to bridge the relationship between core companies and plasma farmers, aiming to establish a mutually beneficial and sustainable partnership. In practice, cooperatives play a strategic role as intermediaries and collective representatives of plasma farmers. However, their role is often limited to administrative functions, with minimal involvement in strategic decision-making processes such as plantation management and profit-sharing arrangements. Using a descriptive-analytical approach based on field data from several plantation areas in East Kalimantan, this research examines key institutional aspects such as governance, transparency, member participation, and power relations between cooperatives and core companies. The findings reveal a significant imbalance in these relationships, as well as weak institutional capacity and low member literacy and engagement. Nevertheless, the study also identifies opportunities for strengthening cooperatives through external support, internal reforms, technological adoption, and multi-stakeholder partnerships. The study concludes that systematic and inclusive institutional strengthening of cooperatives is essential to realizing a more equitable, transparent, and sustainable partnership model.